Comparison of Sorafenib versus Hepatic Arterial Infusion Chemotherapy-Based Treatment for Advanced Hepatocellular Carcinoma with Portal Vein Tumor Thrombosis - Ahn, Young Eun; Suh, Sang Jun; Yim, Hyung Joon; Seo, Yeon Seok; Yoon, Eileen L.; Kim, Tae Hyung; Lee, Young Sun; Yim, Sun Young; Kim, Hae Rim; Kang, Seong Hee; Jung, Young Kul; Kim, Ji Hoon; et al. (Gut and liver, 2021)
Sorafenib is the first approved systemic treatment for advanced hepatocellular carcinoma (HCC). However, its clinical utility is limited, especially in Asian countries. Several reports have suggested the survival benefits of hepatic arterial infusion chemotherapy (HAIC) for advanced HCC with main portal vein tumor thrombosis (PVTT). This study aimed to compare the efficacy of sorafenib-based therapy with that of HAIC-based therapy for advanced HCC with main PVTT. Advanced HCC patients with main PVTT treated with sorafenib or HAIC between 2008 and 2016 at Korea University Medical Center were included. We evaluated overall survival (OS), time-to-progression (TTP), and the disease control rate (DCR). Seventy-three patients were treated with sorafenib (n=35) or HAIC (n=38). Baseline characteristics were not significantly different between groups, except the presence of solid organ metastasis (46% vs 5.3%, p<0.001). The median OS time was not significantly different between the groups (6.4 months vs 10.0 months, p=0.139). TTP was longer in the HAIC group than in the sorafenib group (2.1 months vs 6.2 months, p=0.006). The DCR was also better in the HAIC group than in the sorafenib group (37% vs 76%, p=0.001). Subgroup analysis, which excluded patients with extrahepatic solid organ metastasis, showed the same trends for the median OS time (8.8 months vs 11.1 months, p=0.097), TTP (1.9 months vs 6.0 months, p<0.001), and DCR (53% vs 81%, p=0.030). HAIC-based therapy may be an alternative to sorafenib for advanced HCC with main PVTT by providing longer TTP and a better DCR.